ANALYSIS OF POLITENESS IN JOKO WIDODO'S INSTAGRAM COMMENT COLUMN - Nisa Angelina Silitonga; Selly Febian Sitompul, Sonya Pasaribu, Sonya Steffy Silitonga, Muhammad Natsir (Adisam Publisher, 2024)
This research analysis politeness strategies in Joko Widodo's Instagram comment column using Brown and Levinson's theory. In the era of social media such as Instagram, Facebook, and Twitter, virtual communication exhibits both transactional and interactional functions of language, where the absence of face-to- face communication directly influences participants' language behaviour. This research aims to describe the use of language politeness strategies in virtual interactions. The research method used is qualitative with data collection techniques through observation and recording comments on Joko Widodo's Instagram account. The findings reveal the use of various politeness strategies, including positive politeness, negative politeness, bald-on record, and bald-ofl record strategies. Specifically, the analysis of 1,631 comments showed that 6,2% of the comments used positive politeness strategies, 7,7% used negative politeness strategies, 60% used bald-on-record strategies, and 26,1% used ofl-record strategies. Social factors influencing the choice of these strategies were also identified, underscoring the critical role of politeness in maintaining social harmony and respecting interpersonal relationships in online communication.